What shall we do to boost the immune system of people diagnosed as asymptomatic COVID-19? - Juwalita Surapsari (World Nutrition Journal, 2020)
Nutrition invariably influence the immune system competence and determine the severity of infection. The macro-, micronutrients, and phytonutrients in diet, mainly the fruits and colorful vegetables, generally promote healthy immune response. Thus the adequation of macro- and micronutrient status is an important measure for COVID-19 management to prevent further deterioration.